Mother-infant interactions and infant intake during breastfeeding versus bottle‐feeding expressed breast milk - Alison Ventura; Megan Hupp; Joseph Lavond (Wiley, 2021)
Abstract Bottle‐fed infants are at higher risk for rapid weight gain compared with breastfed infants. Few studies have attempted to disentangle effects of feeding mode, milk composition and relevant covariates on feeding interactions and outcomes. The objective of the present study was to compare effects of breastfeeding directly at the breast versus bottle‐feeding expressed breast milk on feeding interactions. Mothers with <6‐month‐old infants (n = 47) participated in two counterbalanced, feeding observations. Mothers breastfed their infants directly from the breast during one visit (breast condition) and bottle‐fed their infants expressed breast milk during the other (bottle condition). Masked raters later coded videos using the Nursing Child Assessment Parent-Child Interaction Feeding Scale. Infant intake was assessed. Mothers self‐reported sociodemographic characteristics, infant feeding patterns (i.e. percentage of daily feedings from bottles) and level of pressuring feeding style. Mother and infant behaviours were similar during breast and bottle conditions. Percent bottle‐feeding moderated effects of condition on intake (P = 0.032): greater percent bottle‐feeding predicted greater intake during the bottle compared with breast condition. Effects of feeding mode were not moderated by parity or pressuring feeding style, but, regardless of condition, multiparous mothers fed their infants more than primiparous mothers (P = 0.028), and pressuring feeding style was positively associated with infant intake (P = 0.045). Findings from the present study do not support the hypothesis that feeding mode directly impacts dyadic interaction for predominantly breastfeeding mothers and infants, but rather suggest between‐subject differences in feeding experiences and styles predict feeding outcomes for this population.